Therapeutic strategies for preventing skeletal muscle fibrosis after injury - Garg, Koyal; Corona, Benjamin T.; Walters, Thomas J. (Frontiers in Pharmacology, 2015)
Skeletal muscle repair after injury includes a complex and well-coordinated regenerative response. However, fibrosis often manifests, leading to aberrant regeneration and incomplete functional recovery. Research efforts have focused on the use of anti-fibrotic agents aimed at reducing the fibrotic response and improving functional recovery. While there are a number of mediators involved in the development of post-injury fibrosis, TGF-β1 is the primary pro-fibrogenic growth factor and several agents that inactivate TGF-β1 signaling cascade have emerged as promising anti-fibrotic therapies. A number of these agents are FDA approved for other conditions, clearing the way for rapid translation into clinical treatment. In this article, we provide an overview of muscle's host response to injury with special emphasis on the cellular and non-cellular mediators involved in the development of fibrosis. This article also reviews the findings of several pre-clinical studies that have utilized anti-fibrotic agents to improve muscle healing following most common forms of muscle injuries. Although some studies have shown positive results with anti-fibrotic treatment, others have indicated adverse outcomes. Some concerns and questions regarding the clinical potential of these anti-fibrotic agents have also been presented.